PENGARUH TINGKAT NPL TERHADAP PERFORMA PERUSAHAAN PERBANKAN - Sari, Rafika; Pebriani, Reny Aziatul (Jurnal Riset Terapan Akuntansi, 2024)
This research aims to examine the relationship or correlation that exists between the level of non-performing loans and the financial performance of banking companies. The research objects are state-owned banks, namely Mandiri Bank, Indonesian State Bank, State Savings Bank, Indonesian Sharia Bank, Indonesian People's Bank for the last 8 years, namely 2016-2023. The research results are based on a simple regression test with a significance of 0.048. The Non Performing Loan (NPL) variable has a significant negative effect on company performance which is calculated using return on assets. Based on the results it can be seen that Non Performing Loans affect banking performance, therefore companies must maintain and maintain their NPL so that performance can improve the financial performance of banking companies. Keywords: Correlation, Non Performing Loans, Performance, Banking